Analisis Dampak Kesalahan Pemilihan Jurusan terhadap Prestasi Akademik dan Kesejahteraan Psikologis Mahasiswa - Femas Aji Saputra; Adityawarman Adityawarman; Salwa Rahman Nursyabani (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
In education, choosing the right college major is crucial for students to achieve their academic and career potential. However, many students in Indonesia still choose majors that do not suit their interests and talents, which hurts their academic achievement and psychological well-being. This research aims to identify the impact of errors in choosing a major on students' academic achievement and psychological well-being. This research used quantitative methods with a cross-sectional design to collect data from 90 students who experienced a mismatch with their major. The data were analyzed using descriptive and inferential statistical analysis. The research showed that most respondents were dissatisfied with their academic results and often had difficulty understanding lecture material. Most respondents agreed that a mismatch between majors interests and talents can affect academic results, and they frequently feel stressed or depressed because of studying. In conclusion, mistakes in choosing a major can hurt students' academic achievement and psychological well-being. The government and educational institutions must develop more effective and relevant educational programs and provide academic counseling and guidance to help students overcome difficulties and improve their academic performance.